Indigenous Networks: Broadening Insight into the Role They Play, and Contribution to the Academy - Henry, Ella; Mika, Jason Paul; Wolfgramm, Tania (Academy of Management, 2020)
This paper evolved from a study of Maori business networks in New Zealand in 2018. The findings from that study led to an expanded research, based on further case studies with Indigenous peoples in Canada and the United States in 2019. The research contributes to the small but burgeoning Indigenous development literature. It more specifically focuses on the role these networks play, and the ways they raise the social, cultural and spiritual capital of Indigenous communities, which in turn holds the potential to impact on Indigenous enterprise, self-determination and development. This is particularly important, given the shared history of colonial conquest, economic and social disenfranchisement, and the diminution of Indigenous cultures, traditions, and economic and political sovereignty. This study broadens the insight of the academy into Indigenous enterprise, encourages greater collaboration between Indigenous peoples and non-Indigenous scholars, and proposes the idea that networking may enhance spiritual capital for Indigenous and non- Indigenous peoples and enterprise."